2013
DOI: 10.1111/1754-9485.12112
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum immobilisation reduces tumour excursion and minimises intrafraction error in a cohort study of stereotactic ablative body radiotherapy for pulmonary metastases

Abstract: Vacuum immobilisation reduces total tumour excursion, facilitates reproducible positioning and provides robust intrafractional immobilisation during SABR treatments for pulmonary metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
(18 reference statements)
2
20
0
Order By: Relevance
“…reported a mean IFM vector of 1.9 ± 2.5 mm and 1.5 mm ± 1.7 mm when excluding an outlier fraction that required treatment interruption. Interestingly, our IFM results compare favourably to those obtained in previous series of SABR patients immobilized with the BodyFIX device, with mean IFM vectors reported ranging up to 3.0 mm . These variations are partially explained by differences in the practical implementation of the VMAT treatment, including time lapse between on‐line imaging, CBCT‐scan reconstruction, target registration method and implementation of the dual vacuum technology.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…reported a mean IFM vector of 1.9 ± 2.5 mm and 1.5 mm ± 1.7 mm when excluding an outlier fraction that required treatment interruption. Interestingly, our IFM results compare favourably to those obtained in previous series of SABR patients immobilized with the BodyFIX device, with mean IFM vectors reported ranging up to 3.0 mm . These variations are partially explained by differences in the practical implementation of the VMAT treatment, including time lapse between on‐line imaging, CBCT‐scan reconstruction, target registration method and implementation of the dual vacuum technology.…”
Section: Discussionsupporting
confidence: 77%
“…Our results are consistent with those of Siva et al . addressing intrafraction error as well as tumour excursion reduction in SABR patients with pulmonary metastases treated using a similar vacuum immobilization and CBCT‐guided imaging method . With a median time to mid‐treatment CBCT acquisition of 24 min, Siva et al .…”
Section: Discussionmentioning
confidence: 99%
“…28 This is in contradiction to literature, including our own, that suggests vacuum immobilization reduces respiratory-induced motion and has the potential of significant potential clinical effect. 28,29 In these selected cases, consideration of gated delivery may derive a potential benefit to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Boogs et al reported IFV displacements of 1.7 ± 1.0 mm, 2.2 ± 1.3 mm and 2.3 ± 1.3 mm in the x-, y-and z-axes, respectively, utilizing the Bodyfix immobilization system [18]. Validation of the Bodyfix vacuum immobilization system reducing the tumor excursion and the IFV displacements has been previously reported [19,20].…”
Section: Intrafraction Variationmentioning
confidence: 93%